Analysis of Framed Structure with Conventional and Composite Column (International Journal of Innovative Research in Computer Science & Technology, 2022)
The previous few decades have seen  exceptional advances in the utilization of composite  materials in structural applications. Structural members that  are comprised of at least two distinct materials are known  as composite elements. The principle advantage  of composite elements is that the properties of every material  can be joined to frame a solitary unit that performs preferable  generally speaking over its different constituent parts.  Composite columns are a blend of two customary underlying  structures: primary steel and primary cement. As composite  columns were by and large created after steel columns and  supported concrete columns, their plan approach might have  been founded on one or the other steel or substantial plan  techniques. In this thesis G+10, G15, G+30 storey  conventional building models are been compared with  composite column and compared their behaviour under zone  III seismic condition using etabs. Change in the shape and  size of composite column gives better result.
Keywords: Response spectrum analysis; concrete encased steel section; conventional column; Composite column